2010
DOI: 10.1021/ac100083v
|View full text |Cite
|
Sign up to set email alerts
|

Using Microcantilevers to Study the Interactions of Lipid Bilayers with Solid Surfaces

Abstract: We report the use of free-standing microcantilever beams, which have been used as an ultrasensitive method for measuring the surface free energy changes on a substrate induced by the adsorption of thin films, to probe the interactions between a solid surface and a phospholipid bilayer. We relate the observed deflection of a cantilever to the changes in the surface free energy of the solid surface which supports the phospholipid bilayer. We observe that the deflection is influenced by electrostatic and intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Substitution of this value into Equation (1) indicates that the surface stress exerted by the EVs adsorbed on the top Au face is higher than the one exerted by the EVs adsorbed onto the Si face by ∆σ = (28 ± 4) mJ/m 2 . This result can be discussed by taking into account the results reported in the literature about deflection signals upon injection of liposomes onto functionalized SiO 2 and Au surfaces [18]. As already discussed, Liu and co-workers demonstrated that upon incubation with POPC liposomes, a SLB forms on the SiO 2 surface, resulting in a positive deflection due to a compressive stress of ∆σ = (17.0 ± 1.4) mJ/m 2 .…”
Section: Interaction Between Extracellular Vesicles and Microcantileverssupporting
confidence: 54%
See 4 more Smart Citations
“…Substitution of this value into Equation (1) indicates that the surface stress exerted by the EVs adsorbed on the top Au face is higher than the one exerted by the EVs adsorbed onto the Si face by ∆σ = (28 ± 4) mJ/m 2 . This result can be discussed by taking into account the results reported in the literature about deflection signals upon injection of liposomes onto functionalized SiO 2 and Au surfaces [18]. As already discussed, Liu and co-workers demonstrated that upon incubation with POPC liposomes, a SLB forms on the SiO 2 surface, resulting in a positive deflection due to a compressive stress of ∆σ = (17.0 ± 1.4) mJ/m 2 .…”
Section: Interaction Between Extracellular Vesicles and Microcantileverssupporting
confidence: 54%
“…By substituting ∆z into Equation (1) we learn that the layer formation involves a surface work that appears as a surface stress change of ∆σ = (8 ± 1) mJ/m 2 . This result is about half the value reported in the literature for the surface stress measured for the formation of supported lipid bilayer (SLB) on SiO2 surface from POPC liposomes [17,18]. This indicates that the formed layer is not continuous and/or that the formation of the EV layer is less energetic.…”
Section: Interaction Between Extracellular Vesicles and Microcantileversmentioning
confidence: 52%
See 3 more Smart Citations